Plantas melíferas en Venezuela - Stejskal, M. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
A list is presented as the main melliferous plants of Venezuela. They grow in the valley and other humid areas. There are no nectariferous plants in the savannas.